Comments on “Surrogate Gradient Algorithm for Lagrangian Relaxation” - Chang, T. S. (Journal of optimization theory and applications, 2008)
This note presents not only a surrogate subgradient method, but also a framework of surrogate subgradient methods. Furthermore, the framework can be used not only for separable problems, but also for coupled subproblems. The note delineates such a framework and shows that the algorithm can converges for a larger stepsize.